The role of recreational park in creating social interaction within a neighbourhood / Mohamad Shahin Shahdan - Shahdan, Mohamad Shahin (2014)
Social interaction can be defined as how we act and react to the people surround us. It is the way we communicate and interact with each other. Social interaction includes the people that are so close to us such as family and friends or with acquaintances. Having a good social interaction is really important. A good social interaction can helps the neighborhoods to live in a better community. Social interaction can helps to build a harmonious community hence creating a sense of ownership in a community. Besides that, a good social interaction can help the community to get to know each other better and thus can increase the level of safety in a community. It is important to have a place or a space as a community center to bring the people together as a space for social interaction. Recreational park is one of a space provided in a residential area for the community. The community can get to know each other well during the activities they did at the recreational park.